Level of speed abilities of young football players in various training periods - P. Kalinowski; D. Jerszyński; M. Nowakowska (Здоров’я, спорт, реабілітація, 2021)
Purpose: At the highest level of the competition, the players tend to have a comprehensive motor, technical-tactical and mental preparation. It is assumed that in the training process of young players, speed is an important factor determining sports success. Therefore, the aim of the study was to try to compare the speed abilities indicator of young footballers during the summer and winter preparatory period.